The Interconnection of Rural Tourism Development with Local SMEs: The Potential of Startup Business Networking in Southern Malang Indonesia - WINARNO, Agung; AINI, Desti Nur; SALEH, Norlida Hanim Mohd.; ICHWANTO, Muhammad Aris; PURNOMO, Agus; RAHMAN, Amalia Arifah (Journal of Environmental Management and Tourism, 2024)
The purpose of this research is to assess the performance of rural tourism destinations and local small and medium enterprises (SMEs) while exploring their potential for integrated tourism destination development in the Southern Malang region. The research employs an action research case study approach where numeric data are generated through the distribution of Likert-scale questionnaires and analyzed using clustering. The results of the clustering are described using SWOT analysis, which aims to identify prospects and the levels of development for tourism destinations and SME performance. The stages involved are as follows: problem or issue identification, action planning, action implementation, data collection during or afteraction implementation, data analysis and result evaluation, reflection and reconsideration of the actions taken, and decision-making regarding subsequent steps based on the evaluation results. The research findings indicate that the level of rural tourism in the Southern Malang region falls into the pioneering category with a limited variety of destinations. This is attributed to the insufficient infrastructure and the lack of standout rural tourism products, as well as the limited supporting infrastructure such as roads, bridges, information centers, souvenir shops, and weak cellular signal coverage. Additionally, community awareness and support are relatively lacking in contributing to tourism development, and the regional government's support, in terms of institutional establishment and investment actions, is still in its infancy. SME performance shows better progress compared to the advancement of the tourism sector. Thus, if the tourism sector can develop, it has the potential to enhance the performance of local SMEs. The contribution of the rural tourism sector in Southern Malang to economic growth and the development of SMEs is still relatively insignificant. SMEs have grown with limited technology application, and their market areas are predominantly local. The innovation's contribution to increasing income in the Southern Malang region will be evident through increased tourist numbers, sales of SME products, and enhanced competitiveness of the region in the tourism and business markets. In this context, it is essential for the government, businesses, and local communities to collaborate in developing sustainable innovative strategies.